Natural disasters and social capital formation: The impact of the Great Hanshin-Awaji earthquake - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2013)
The Great Hanshin-Awaji (Kobe) earthquake struck Japan in 1995, causing devastating damage to the economic landscape of south-central Japan. The earthquake also caused people to realize the importance of social capital in Japan. Based on a large, individual-level database comprising 488,223 observations, this study investigated how, and the extent to which, the earthquake enhanced the investment in social capital through participation in community activity. The differences-in-differences method was used, and the following key findings were obtained: (1) In Japan, people were more likely to invest in social capital in 1996 than in 1991, (2) the effects of the earthquake decreased as the distance of one's place of residence increased from Kobe, and (3) the earthquake significantly increased the social capital investment rate of Kobe residents, whereas it had no significant influence on the investment rate of residents of large cities close to Kobe.
Keywords: N35; Q54; Z13; 330; Natural disasters; social capital; volunteer activities